2017
DOI: 10.1038/s41598-017-01441-9
|View full text |Cite
|
Sign up to set email alerts
|

Invisible body illusion modulates interpersonal space

Abstract: Interpersonal space (e.g., IPS) refers to the physical distance individuals maintain from others during social interactions, and into which intrusion by others can cause discomfort. Here, we asked whether the size of IPS is affected by manipulation of one’s own body representation. To address this issue, in Experiment 1, IPS was measured through a comfort-distance task, before and after eliciting the illusion of owning an invisible body. To rule out a general, nonspecific change in space perception consequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 51 publications
3
21
0
Order By: Relevance
“…To further confirm this conclusion in the future it will be important to replicate the findings of the current report while equally measuring PPS via other “traditional” approaches. That is, as argued by several different other authors 44 , 45 , 51 , 79 , it is possible that different PPS representations exist, and the interrelation between multisensory PPS defined via reaction times 25 , 26 , PPS as defined by defensive reflexes 57 , reaching space 41 , 80 , and now the method developed here, is unclear. It is unequivocal that here we demonstrate a multisensory coupling that is space-dependent, yet how this spatial extent relates to, say, the spatial region within which tactile reaction times are facilitated 27 (a more classic definition of PPS) remains an open question.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…To further confirm this conclusion in the future it will be important to replicate the findings of the current report while equally measuring PPS via other “traditional” approaches. That is, as argued by several different other authors 44 , 45 , 51 , 79 , it is possible that different PPS representations exist, and the interrelation between multisensory PPS defined via reaction times 25 , 26 , PPS as defined by defensive reflexes 57 , reaching space 41 , 80 , and now the method developed here, is unclear. It is unequivocal that here we demonstrate a multisensory coupling that is space-dependent, yet how this spatial extent relates to, say, the spatial region within which tactile reaction times are facilitated 27 (a more classic definition of PPS) remains an open question.…”
Section: Discussionmentioning
confidence: 83%
“…Given these results, in a first aim here we sought to further probe the putative relation between bodily self-consciousness and PPS by examining whether the latter representation was “preserved yet modified” when the body was rendered invisible. This specific hypothesis is supported by the above-mentioned findings that embodiment, putatively reliant on PPS encoding 20 , 33 35 , over empty spaces is possible 42 , 43 , yet interpersonal space – a concept closely related but not identical to PPS (see see Clery & Ben Hamed 44 and Hunley & Lourenco 45 ) – is contracted 41 when the body is rendered invisible.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…More directly related to bodily self‐consciousness, a number of groups have shown that tactile stimulation of the body is not necessary to induce bodily illusions, but solely implying tactile sensation emanating from the PPS may elicit changes in bodily representation . Furthermore, these tactile predictions may have a phenomenological correlate .…”
Section: Bodily Self‐consciousnessmentioning
confidence: 99%
“…The Dosey-Meilsels Protection Theory [4], assigns personal space to protection objectives from a physical attack towards one's body or social attack towards one's social image, whereas [5] attributes it to navigation's planning objectives. Hence, [6,7,8] demonstrated that there are two different types of personal spaces. They are linked to different high-order representations of the body.…”
Section: Proxemics Theorymentioning
confidence: 99%